Management of Diabetic Retinopathy - Nova Herdana; AK Ansyori; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2018)
Introduction. Diabetic retinopathy (RD) is one of the most common complications of diabetes mellitus, and is a major cause of blindness in patients aged 20-64 years worldwide. The main principle of the management of RD is to prevent, inhibit and overcome complications that occur. Vitrectomy, laser photocoagulation, intravitreal anti VEGF injection become modalities in RD therapy. If PDR has occurred, vitreous hemorrhage can occur or the retina is attracted by proliferation tissue, vitrectomy should be performed. Case Presentation. The patient is a 52-year-old man who came with the main complaint that both eyes have blurred slowly since ± 6 months ago. Blurred vision is not accompanied by red eyes, there is smoke-like vision. In the past the history of the disease obtained a history of DM 15 years of irregular control and hypertension of 3 years with regular control, a history of spectacles present. The ophthalmological examination of the right eye revealed a vision of 6/30 pH (-), TIOD within normal limits, and a grade II nuclear cataract in the lens. Right eye fundoscopy revealed decreased foveal reflexes and exudates in the macula, dot, blot, flame-shaped bleeding in 4 quadrants of the retina, exudate, venous beading, micro-aneurism. Management in these patients is pars plana vitrectomy, endolaser, and intravenous OS anti-VEGF injection under general anesthesia. Whereas the right eye was intravitreal photocoagulation laser and anti-VEGF laser (done 2 weeks before). Conclusion. A case of advanced left eye PDR with severe NPDR and right eye DME and grade II nuclear cataracts has been described in both eyes. Patients treated with laser photocoagulation in the right eye. In the left eye pars plana vitrectomy, endolaser, and intravitreal bevacizumab injection. Sharp vision of the left eye progressed postoperatively.